195 Delayed transfer of care (DToC) in neuroscience across South London: an insight through patient journeys. Issue 6 (27th May 2022) - Wu, Kit; Liu, Yan; King, Rachel; Ellis, Cathy; Nirmalananthan, Niran; Weeks, Rob; Isaacs, Jeremy; Dilley, Michael
Abstract : Introduction: Patients with complex neurological problems often require admission to a regional neuro- science centre to undergo further investigations and treatments not available in their local hospitals. A 'delayed transfer of care' (DToC) occurs when a patient is ready to be discharged but is still occupying a bed. Financially, this cost £104 million in London alone where 18% of all occupied beds are due to DToC [NHSE 2016]. Objectives: To investigate causes of DToC for Neuroscience patients between regional Neuroscience units [King's College and St George's Hospitals (KCH and SGH respectively)] and DGHs in the South London region. Method: We reviewed notes of 28 neurological patients admitted to KCH from surrounding DGHs between March 2018 to June 2019. Key events of the repatriation process in relation to the patient's hospital journey were analysed. Results: Sixteen male and twelve female patients [mean age 58.5 years (29–89)] were admitted to KCH with a median length of stay of 21.5 days, of which 8.5 days were due to delays in the internal repatriation process and 3.5 days to time waiting for an available bed at their corresponding DGH. Conclusion: In addition to traditional DToC data, we found further internal delays not previously captured. Cause analysis showed this to be a bidirectional problem. Collection of further datasets, facilitated by ODN, will help to determine variation in DToC for hospitals within a network and guide solutions. kitwu@doctors.org.uk